2002
DOI: 10.1081/clt-120014646
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Amatoxin Poisoning: 20-Year Retrospective Analysis

Abstract: Benzylpenicillin (Penicillin G) alone and in association was the mostfrequently utilized chemotherapy but showed little efficacy. No benefit was found for the use of thioctic acid or steroids. Chi-square statistical comparison of survivors and dead vs. treated individuals supported silybin, administered either as mono-chemotherapy or in drug combination and N-acetylcysteine as mono-chemotherapy as the most effective therapeutic modes. Future clinical research should focus on confirming the efficacy of silybin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
276
3
35

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(317 citation statements)
references
References 187 publications
3
276
3
35
Order By: Relevance
“…It was reported that silybin which was derived from Silybum marianum herb, and was water-soluble substance of silimarine derivative, decreased entrances of amatoxins into cells, so that they showed hepatoprotective effect [21] .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that silybin which was derived from Silybum marianum herb, and was water-soluble substance of silimarine derivative, decreased entrances of amatoxins into cells, so that they showed hepatoprotective effect [21] .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining six cases were managed according to overseas experience in the treatment of amatoxin poisoning. [10][11][12] Treatment included intravenous silibinin, oral silymarin, intravenous Nacetylcysteine, oral multiple-dose activated charcoal, high-dose intravenous penicillin, and early charcoal haemoperfusion. Two local cases progressed to liver failure and required liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The antidotes benzylpenicillin, ceftazidime, Nacetyl-cysteine (NAC), rifamycin, and silibinin have been advocated by some [26,34,36,88,[110][111][112], and questioned by others [113,114]. Of these, silibinin and NAC show the most promise [32,34,111,115]. Magdalan [34] performed cell culture studies and found that hepatocytes poisoned with alpha-amanitin and simultaneously treated with NAC or silibinin showed less evidence of lipid peroxidation than poisoned hepatocytes simultaneously treated with benzylpenicillin or without an antidote treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…It is a scavenger of free radicals, has anti-inflammatory effects, stimulates protein synthesis, and inhibits amatoxin uptake by hepatocytes [26,34]. If silibinin is available, its administration seems reasonable [19,31,85,97,111,115,116]. Silibinin could potentially be obtained by contacting the researchers using this antidote through clinicaltrials.gov, using identifier NCT00915681.…”
Section: Treatmentmentioning
confidence: 99%